Performance Analysis of Front-Line Demonstrations on Green Gram (Vigna Radiate l.) in Jodhpur District of Western Rajasthan - Puniya, Manmohan; Choudhary, Desh Raj (International Journal of Environment, Agriculture and Biotechnology, 2024)
Pulses being rich in quality protein, minerals and vitamins are inseparable ingredients of diet of majority of indian population. Despite high nutritive value of pulses and their role in sustainable agriculture desired growth rate in production could not be witnessed. The domestic production of pulses is consistently below the targets and actual domestic requirements are also higher, due to this pulses are being imported. The Krishi Vigyan Kendra, Jodhpur-II (Phalodi) has carried out frontline demonstrations on greengram crop varieties GM-6 and IPM 205-7 covering an area of 30 ha of farmer's field to exhibit latest production technologies and compared it with farmer's practice. The study in total 50 frontline demonstrations were conducted on farmer's fields in villages viz. Kali-mali and Baori of Jodhpur district of Rajasthan state during 2020 and 2022, to demonstrate production potential and economic benefit of improved technologies comprising sowing method, nutrient management and chemical weed management and adoption of whole package of practices for crop. After sowing of seed, application of weedicide Imazethapyr 10SL as early post emergence at 50 gm a.i. per ha in 500 liters of water used for effective control of the weeds during kharif season in rainfed condition. The findings of the study revealed that the demonstrated technology recorded a mean yield of 687 kg/ha which was 23.7 % higher than obtained with farmers practices (555 kg/ha). Higher mean net income of Rs. 31285/ha with a Benefit:cost ratio of 3.05 was obtained with improved technologies in comparison to farmers practices (24710).The frontline demonstrations conducted on greengram crop at farmer’s field revealed that the adoption of improved technologies significantly increased the yield as well as yield attributing traits of crop and also the net neturns higher than the farmer’s practices. So, there is a need to disseminate the improved technologies among the farmers with effective extension methods like training and demonstrations. The farmers should be encouraged to adopt the recommended package of practices realizing for higher returns.